Kreativitas, Minat Belajar MENINGKATKAN KREATIVITAS DAN MINAT BELAJAR SISWA MATERI PERUBAHAN LINGKUNGAN DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING - Nur Anggraini, Desti; Atip Nurwahyunani; Rahayu, Praptining (Jurnal Biogenerasi, 2024)
This study aims to spesified the effectiveness of implementing the Project Based Learning model in increasing creativity and interest in learning environmental change material in semester I classroom learning X-1 SMA Negeri 15 Semarang for the 2024/2025 academic year. The subjects in this research are 35 students in class X-1 of SMA Negeri 15 Semarang. This research design takes the research procedures of the classroom action research model which is adapted from Hopkins. Every cycle includes four stages, namely planning, implementation, observation and reflection. Research data consists information regarding the educational results and experiences of the PjBL model are based on data collected through observation techniques, interviews, questionnaires and documentation. The research results show an increase in average creativity score from 66.85% in cycle I to 85.70% in cycle II. Student interest in learning also showed progress from cycle I of 67.85%, increasing to 86.42% in cycle II. The students perception to the implementation of the PjBL learning model had a very good impact, which can be observed from students enthusiasm during learning and from the educational results of the questionnaires filled out by the students. This can be caused by the fact that when students face challenges that match their respective abilities, students are more motivated to complete the answers well. The educational results of this research are considered successful because of the level of interest in learning for all students is at a high percentage, namely 86.42%.